Influencing mechanism of silica fume on early-age properties of magnesium phosphate cement-based coating for hydraulic structure. (15th August 2022) - Ma, Cong; Liu, Yuantao; Shi, Jinyan; Zhang, Aijun; Song, Danqing; Zhou, Haijun; Du, Yanliang
Abstract: The current research systematically investigated the influencing mechanism of silica fume (SF) on early-ages properties (within 3 d) of an inorganic repairing coating-magnesium phosphate cement (MPC). It was determined by strength measurement, chemical effect test, hydration product characterization, microstructure observation, low-filed nuclear magnetic resonance (LF-NMR), and AC impedance spectroscopy (ACIS) record. The results show that SF can improve the early-ages mechanical property of MPC. The compressive strength of SF6 (adding 6% SF) at 1 h and 3 d are 26.0 and 51.9 MPa, respectively, which satisfies the strength requirement of repairing coating for hydraulic structure. In the MPC system, SF plays the role of nucleation and filling effect, which accelerates its hydration process and improves the compactness of the matrix. SF is chemical inert to the acidic component-ammonium dihydrogen phosphate (ADP) in MPC, while the reaction between SF and MgO can be activated. Thus, the amorphous magnesium silicate hydrate (M-S-H) is suspected to be formed in SF-MPC. LF-NMR and ACIS test results show that SF can increase the hydration rate, reduce the porosity, and improve pore structure. The current results are helpful to further improve the property of MPC-based inorganic repairing coating for hydraulic structure. Highlights: The modification mechanism of SF for MPC is discussed. SF can improve the early-ages mechanical property of MPC. The reaction between SF and MgO can be activated in MPC.